2016
DOI: 10.12678/1089-313x.20.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Preseason Aerobic Fitness Screening in Professional and Pre-professional Modern Dancers

Abstract: The aerobic demands of today's dance repertoire warrant understanding of the current cardiorespiratory fitness of dancers. The purpose of this study was to compare aerobic fitness levels of professional and pre-professional modern dancers and determine change over time. A retrospective analysis of four groups, two professional, and two pre-professional, was conducted in preseason annual screens, occurring before the professional dancers' rehearsal period and the students' academic training. Resting (HRrest), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Two studies have indicated that professional dancers have better aerobic fitness than pre-professional dancers. 31,32 This may suggest that professional dancers are exposed to more appropriate training for their work demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have indicated that professional dancers have better aerobic fitness than pre-professional dancers. 31,32 This may suggest that professional dancers are exposed to more appropriate training for their work demands.…”
Section: Discussionmentioning
confidence: 99%
“…9 This indicates that pre-professional dance training, during which students are primarily exposed to class and rehearsal, may not adequately prepare a dancer for the performance demands of being a professional. It has been shown that professional dancers have better aerobic fitness compared to preprofessional dancers, [31][32] and lesser aerobic fitness levels have been associated with the number of injuries sustained in ballet students. 33 Decreased lower body muscular power has been linked to days lost due to injury in contemporary dance students.…”
Section: A Systematic Reviewmentioning
confidence: 99%
“…4,8 Indirect links have, however, been drawn between cardiorespiratory fitness and performance ability, through significant differences documented between fitness levels in dancers of different ranks in classical ballet (principals, soloists, first artists, and corps de ballet/ artists) [17][18][19] and in student and professional contemporary dancers. 20 Through the previous body of available literature, the extent to which a dancers' cardiorespiratory fitness level is directly related to the performance ability of that dancer is not all-together clear. It seems that professional dancers, and higher ranked professionals in ballet, have greater cardiorespiratory capacity than students, 5,20 and lower ranked professionals in ballet, [17][18][19] but correlational studies have found no significant relationship between aerobic fitness measures and measures of aesthetic competence.…”
Section: Introductionmentioning
confidence: 99%
“…20 Through the previous body of available literature, the extent to which a dancers' cardiorespiratory fitness level is directly related to the performance ability of that dancer is not all-together clear. It seems that professional dancers, and higher ranked professionals in ballet, have greater cardiorespiratory capacity than students, 5,20 and lower ranked professionals in ballet, [17][18][19] but correlational studies have found no significant relationship between aerobic fitness measures and measures of aesthetic competence. 4,8 A number of benefits to higher cardiorespiratory fitness levels amongst dancers are seen to exist; however, we are currently only at the beginning of our understanding of how this translates in an individual dancer's outwardly visible skill and overall performance ability.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that blocks of performances brought about increases in aerobic fitness parameters of professional contemporary dancers [29]. Furthermore, professional contemporary dancers showed higher levels of aerobic fitness than pre-professional students, which is likely a reflection of their greater performing schedules [30]. For dance students, a majority of time is spent developing technique through classwork [31], whereas professional dancers, having already established a solid technical base, spend a larger proportion of their day rehearsing and performing.…”
Section: What Are the Physiological Requirements Of Dance?mentioning
confidence: 99%